A pilot infrastructure for searching rainfall metadata and generating rainfall product using the big data of NEXRAD. (July 2019) - Seo, Bong-Chul; Keem, Munsung; Hammond, Raymond; Demir, Ibrahim; Krajewski, Witold F.
Abstract: The Iowa Flood Center (IFC) developed a pilot infrastructure to explore rainfall metadata (descriptive statistics) and generate rainfall products over the Iowa domain based on the NEXRAD Level II data directly accessible through cloud storage (e.g., Amazon Web Services). Known as IFC-Cloud-NEXRAD, it resembles the Hydro-NEXRAD portal that provided researchers with ready access to NEXRAD radar data. Taking advantage of the cloud storage benefits (unlimited storage and instant access), IFC-Cloud-NEXRAD reduces the common challenges of most data exploration systems, which often lead to massive data acquisition/ingestion and rapid filling of limited system storage. Its map-based interface allows researchers to select a space-time domain of interest, retrieve and visualize pre-calculated rainfall metadata, and generate radar-derived rainfall products. Because the system provides generalized approaches to compute metadata and process data for rainfall estimation, the framework presented in this study would be readily transferrable to other geographic regions and larger scale applications. Highlights: IFC-Cloud-NEXRAD demonstrates utility of the NEXRAD Level II data accessible through the cloud storage. The system offers metadata search and visualization, as well as rainfall product generation. The system reduces temporal and spatial restriction arising from the limited system storage.